Morphological and secretory dysfunction of left atrium in Marfan syndrome. (14th October 2021) - Ernst, L; Zhang, K; Pieske-Kraigher, E; Pieske, B; Heinzel, F R; Gehle, P
Abstract: Introduction: Marfan syndrome (MFS) is characterized by a mutation in the FBN1-gene which leads to a structural deficiency of the extracellular matrix component fibrillin-1 and a dysregulation of TGFβ. In recent years, cardiac remodeling with systolic and/or diastolic left ventricular dysfunction was shown in some MFS patients (Marfan Cardiomyopathy). Interestingly, in animal studies it has been shown that fibrillin-1 is abundantly present in atria and that TGFβ overexpression leads to atrial but not ventricular fibrosis (1, 2). However, the role of MFS for atrial remodeling and secretion (NT-proBNP) is unclear. Purpose: To assess morphological and secretory function of the left atrium (LA) in patients with MFS and its relationship to left ventricular function. Methods: We retrospectively analyzed echocardiographic and laboratory data in 307 Patients with MFS and in 147 healthy controls who had presented at our Marfan clinic between 23 February 2016 and 15 June 2020. At every visit, echocardiography had been carried out and NT-proBNP levels had been taken. A two-level mixed effects model was now performed to compare left atrial size between patients with MFS and controls. Results: Left atrial size was significantly increased in patients with Marfan syndrome with and without aortic operation in medical history compared with controls (adjusted means: 18.4cm 2 and 17.6cm 2 vs. 15.5cm 2 p<0.05). Body surface area (6.12, 95% CI: 4.26, 7.98 p<0.001), age (0.06, 95% CI: 0.02, 0.1 p<0.01), E/e' (0.3, 95% CI: 0.14, 0.46 p<0.001) and EF (−0.05, 95% CI: −0.10, −0.01 p=0.011) were significantly correlated with LA size. NT-proBNP was also increased, after logarithmic transformation, mean difference between unoperated patients with MFS and controls was 0.34 (95% CI: 0.11, 0.57 p=0.004). Interestingly, NT-proBNP and LA size both were increased also in patients with normal left ventricular filling pressures, assessed by E/e' (see Figure 1). For increased LV filling pressures (E/e'>8), regression analyses revealed a more extensive dilatation of LA size in patients with MFS for further increase of E/e' compared to controls, although not significant for the latter. Haploinsufficiency mutations were associated with significant higher levels of NT-proBNP than dominant-negative (p=0.043) (see Figure 2), although this could not be shown for LA size. Atrial fibrillation (AF) tended to be more common in Marfan group (17/307 to 4/147, χ 2 (1) = 1.79, p=0.181) but most patients with AF also had prior aortic operation. Conclusions: Our data show that Marfan syndrome is associated with left atrial dilatation, accompanied by increased levels of NT-proBNP which seem to be independent of elevated left ventricular filling pressure. This supports the idea of a primary impairment of cardiac function. If this leads to an impaired clinical outcome, e.g. characterized by increased prevalence of AF and stroke, needs be investigated by further research. FUNDunding Acknowledgement: Type of funding sources: None.